The authority of scripture in reformed theology: truth and trust - Belt, Henk van den (Studies in reformed theology, 2008)
Truth and certainty-- Calvin's Institutes -- Source and sense -- Reformed orthodoxy -- Benjamin B. Warfeld -- Herman Bavinck -- Trusting the truth